Design and fabrication of variable temperature sensor on cast iron at tilting furnace / Muhammad Zuhrilhakim Ab Maulub - Ab Maulub, Muhammad Zuhrilhakim (2022)
This study about temperature sensor on cast iron using tilting furnace. The problem of this study is there is no temperature sensor yet in the foundry laboratory, so a temperature sensor must be created for the molten cast iron. It is harder to measure the temperature of molten cast iron without a temperature sensor. The other problem is the high temperature of molten cast iron is too dangerous for people as it is too hot to be measured by using a thermometer. People can't measure the temperature of molten cast iron manually. This study is to design the temperature sensor at the tilting furnace at the foundry laboratory and to fabricate the temperature sensor of molten metal for cast iron at the tilting furnace. The wire and the circuit will be attached to the temperature sensor so as to be able to emit a danger sound when the temperature of the molten cast iron in impact rises to a high temperature. The sensor will detect the changed of the temperature and will display an output at the monitor. This study require to create a design in solid works for the temperature sensor. This feature are to measure the temperature of molten cast iron and to verify the maximum temperature of molten cast iron. This study will make a design and fabrication more effective because the design can detect the high temperature of molten cast iron and make an alert sound when the temperature rising.